2018
DOI: 10.1016/j.jpowsour.2018.08.024
|View full text |Cite
|
Sign up to set email alerts
|

On the strange case of divalent ions intercalation in V2O5

Abstract: HIGHLIGH TS • Controversial reports exist in the lit erature regarding Ca/Mg intercalation in V 2 0 s-• Crystal structure elucidation of inter calated phases bas remained elusive to date. • Electrochemical and ex"'5itu XRD ex periments evidenoe formation of pro tonated phases. • Degradation of V 2 0s bas also been observed un der some conditions. • Oxidation of AV20s (A= Ca, Mg) prepared by solid state reaction was not feasible.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
70
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(75 citation statements)
references
References 49 publications
2
70
0
Order By: Relevance
“…However, there is a question about what really cycles in this configuration. As demonstrated by Verrelli et al the electrochemical process that occurs in V 2 O 5 cathodes in the presence of Mg cations in dry and wet alkyl-carbonate-based electrolyte solutions is related to protons insertion rather than to Mg ions insertion 49. …”
mentioning
confidence: 96%
“…However, there is a question about what really cycles in this configuration. As demonstrated by Verrelli et al the electrochemical process that occurs in V 2 O 5 cathodes in the presence of Mg cations in dry and wet alkyl-carbonate-based electrolyte solutions is related to protons insertion rather than to Mg ions insertion 49. …”
mentioning
confidence: 96%
“…In addition, Palacín et al. [ 100 ] evaluated the feasibility of α‐V 2 O 5 as a CIB cathode material in different temperatures and moisture conditions. In a dry alkyl carbonate‐based electrolyte, no electrochemical activity was observed at either room temperature or 55 °C.…”
Section: Cathode Materialsmentioning
confidence: 99%
“…Detailed analysis has revealed that many literature reports of reversible Mg intercalation were more likely to result from parasitic electrolyte decomposition and proton intercalation. 15 Indeed, a recent perspective has highlighted the disparity between reported capacities of Mg battery cathodes and the capacity verified by elemental, redox, and structural changes in the oxide host. 16 For this reason, reported capacities should not be directly equated with Mg intercalation activity without robust supporting evidence.…”
Section: Introductionmentioning
confidence: 99%
“…17 While many different structures and compositions of vanadium oxides and phosphates have been investigated for Mg batteries, most have only demonstrated reversible Mg intercalation in the presence of water (either in the electrolyte or contained in the structure), such as VO x nanotubes, 18,19 cathode materials, respectively, and that any additional reactivity could be attributed to parasitic reactions and proton intercalation. 15,22 Therefore, the postulated enhancement of Mg intercalation by water inclusion has been cast in serious doubt, and rigorous studies of electrode materials should be conducted in anhydrous environments.…”
Section: Introductionmentioning
confidence: 99%